Clustering-based dynamic privacy preserving method for social networks - Yong-hao GU; Jiu-chuan LIN; Da GUO (Tongxin xuebao)
Due to the dynamic characteristics of the social network graph structure,an effective dynamic privacy preserving method was needed.To solve the problems of the existing dynamic privacy preservation methods,such as attacker’s too little background knowledge and the low adaptability to the dynamic characteristics of graph structure,a clustering-based dynamic privacy preservation method was provided.The analysis shows that the proposed method can resist many kinds of background knowledge attacks and has good adaptability to the dynamic characteristics of the social network graph structure.